Retaining mathematical momentum: Investigating the impact of flipped classroom model on mathematics retention among senior secondary school students - Akorede Ayoola Asanre; Sondlo Aviwe; Abdullateef A. Adedeji (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: This study investigates the impact of the flipped classroom model on the retention of mathematical concepts among senior secondary students in Ogun State, Nigeria, with attention to gender-based differences.Aims: The study aims to examine both the main and interaction effect of strategies (flipped classroom model and conventional approach) and gender on the retention of secondary school students in mathematics in Ogun State, Nigeria. Having in mind to retain mathematical momentum within secondary school students in Ogun State.Method: Employing a quasi-experimental, non-equivalent control group design, the study compared retention scores between an experimental group using the flipped classroom model and a control group taught with traditional methods. Fifty-four Senior Secondary School II students were selected from two schools and divided evenly between the groups. Data was collected through pre-tests, post-tests, and delayed post-tests using the Mathematics Retention Test (MRT) with the reliability coefficient of 0.74. Analysis of Covariance (ANCOVA) was used to analyze the data.Results: The outcomes showed that students in the flipped classroom model had much better retention scores than those in conventional environments, therefore underscoring the success of the flipped model in encouraging long-term retention. Furthermore, results revealed that the approach helped male and female students equally; there was no appreciable relationship between gender and retention results. These findings highlight the possibilities of the flipped classroom as an inclusive and successful teaching tool to improve mathematical retention.Conclusion: The study concluded that the flipped classroom approach improves mathematical retention in Ogun State, Nigeria, without allowing any gender gap. Additionally, it shows that flipped classroom model help to retain the mathematical momentum of the students sampled. Adopting the flipped classroom model will help schools in Ogun State optimize their advantages for different student groups by means of teacher preparation and digital resource support.